THE LHC AND THE DISCOVERY OF THE HIGGS BOSON:50 YEARS OF HIGGS MECHANISM - Royon, C. (Одеські астрономічні публікації, 2014)
We describe briefly the ATLAS detector and some of the physics results on QCD, top physics and. the Higgs boson discovery that lead to the Nobel Prize of Physics in 2013. We finish the short report by a new method to look for extra-dimensions in the universe.